THE VARIABILITY OF PEANUTS CULTIVARS IN THE NORTH TRANSCASPIAN CONDITION - L. P. Podolnaya; A. G. Doubovskaya; M. Sh. Asfandiiarova; R. K. Tuz; E. O. Migacheva (Труды по прикладной ботанике, генетике и селекции)
Analyzed environmental correlations between economically valuable traits of two varieties of peanuts (Arachis hypogaea L.) of different origin - ‘Krasnodarec 14’ and ‘Tashkentskij 32’. The study was conducted in the North of the Astrakhan region on the basis of Prikaspiiskii nauchno-issledovatel'skiiinstitut aridnogo zemledeliya (PNIIAZ) in the North of the Astrakhan area for 6 years. Identified correlations, describing the particular samples. The study showed that the sample from Uzbekistan is better adapted to the conditions of the Astrakhan region.